Value Added and Productivity Linkages Across Countries - François de Soyres (Oesterreichische Nationalbank (OeNB), 2016)
What is the relationship between international trade and business cycle synchronization? Using data from OECD countries, I find that trade in intermediate inputs plays a significant role in synchronizing GDP fluctuations across countries while trade in final goods is found insignificant. Motivated by this new fact, I build a model of international trade in intermediates that is able to replicate more than 70% of the empirical trade-comovement slope, making a significant step toward solving the "Trade Comovement Puzzle". The model relies on two key assumptions: (i) price distortions due to monopolistic competition and (ii) fluctuations in the mass of firms serving each country. The combination of those ingredients creates a link between domestic productivity and foreign shocks through trade linkages. Finally, I provide evidence for the importance of those elements in the link between foreign shocks and domestic GDP and test other predictions of the model.
Keywords: F12; F17; F4; F62; L22; 330; International Trade; International Business Cycle Comovement; Networks; Input- Output Linkages